Spring 프레임워크 AOP의 UML/XML 확장 표현 및 변환 기법 - 이후재(Hoo-Jae Lee); 류성열(Sung Yul Rhew); 김종배(Jong-Bae Kim) (디지털콘텐츠학회논문지, 2010)
오픈 소스 프레임워크 기반의 Spring AOP에는 명세화를 위한 지침이나 표준이 없어 개발과 유지보수에 혼란을 야기 시키고 있으며, 특히 기존의 MVC 모델, Struts 프레임워크에서 사용하는 AOP 모델 연구와 UML 다이어그램과의 불일치 문제는 Aspect의 재사용을 더욱 어렵게 하고 있다. 본 연구는 기존의 MVC 모델, Struts 프레임워크에서 사용하는 AOP 모델의 혼용을 Spring AOP에서 수용 처리하기 위하여, Aspect, Pointcut과 Advice를 UML과 XML로 어느 것으로 표현하여도 가능할 수 있도록 기존의 표현법을 확장하여 제시하고, 제시된 표현 기법이 상호변환 가능할 수 있도록 관계성을 정의한 후, 상호변환의 사례를 보여 개발과 유지보수를 용이하게 함을 입증 하였다. 또 Aspect의 재사용을 보다 효율적으로 활용하기 위한 패키지화 방법을 제안하고 그 재사용 가능성을 검증하였다. There is no guideline or standard for the specification of the open-source-framework-based Spring AOP, and it causes confusion in development and maintenance. Moreover, the inconsistency between the existing MVC model, the AOP model that is used for Struts framework and the UML diagram makes the aspect reuse more difficult. In this study, a widened existing method was proposed so that Aspect, Pointcut and Advice could be expressed by either UML or XML to ensure that the Spring AOP can accept the combined use of the existing MVC model and the AOP model, which is used for Struts framework. Relationship was defined so that the mutual conversion could be possible with the proposed expression method, and the realization of simple development and maintenance was verified via the examples of mutual conversion. In addition, a packaging method to efficiently reuse aspect was proposed, and the possibility of reuse was verified. KCI Citation Count: 1